Limits of Conceivability in the Study of the Future. Lessons from Philosophy of Science - Virmajoki Veli (Elsevier, 2022)
In this paper, the epistemological and conceptual limits of our ability to conceive and reason about future possibilities are analyzed. It is argued that more attention should be paid in futures studies on these epistemological and conceptual limits. Drawing on three cases from philosophy of science, the paper argues that there are deep epistemological and conceptual limits in our ability to conceive and reason about alternatives to the current world. The nature and existence of these limits are far from obvious and become visible only through careful investigation. The cases establish that we often are unable to conceive relevant alternatives; that historical and counterfactual considerations are more limited than has been suggested; and that the present state of affairs reinforces its hegemony through multiple conceptual and epistemological mechanisms. The paper discusses the reasons behind the limits of the conceivability and the consequences that follow from the considerations that make the limits visible. The paper suggests that the epistemological and conceptual limits in our ability to conceive and reason about possible futures should be mapped systematically. The mapping would provide a better understanding of the creative and critical bite of futures studies.